Kekuatan Hukum Perjanjian Perkawinan Yang Dibuat di Luar Negeri Oleh Warga Negara Asing (WNA) Yang Telah Menjadi Warga Negara Indonesia (WNI) di Indonesia - Elizabeth Chen; Jamin Ginting (Cerdika: Jurnal Ilmiah Indonesia, 2025)
A Prenuptial Agreement is an agreement or agreement made by a husband and wife which is intended to regulate the consequences of marriage on the assets of the husband and wife, before or during the marriage. In practice, there are problems that arise regarding this Prenuptial Agreement, namely a Prenuptial Agreement made by a foreign citizen couple abroad whose marriage registration was also carried out in Indonesia, but in this case the Defendant had become an Indonesian citizen before their marriage was registered in Indonesia and then there was a lawsuit for the division of assets in the form of land belonging to the husband. The formulation of the problem in this research is How is the Legal Force of a Prenuptial Agreement made Abroad by a Foreign Citizen (WNA) who has become an Indonesian Citizen (WNI) in Indonesia. The purpose of this study is to examine the concept of regulating Prenuptial Agreement in Indonesia. The benefits of this study are to provide additional knowledge in the field of legal science, especially in Prenuptial Agreement. The Prenuptial Agreement made by a foreign citizen couple in Italy in this case is binding on the parties because the parties acknowledge the existence of a Prenuptial Agreement. However, legally if the Prenuptial Agreement is not made with a notary deed domiciled in Indonesia and is not legalized by a marriage registrar, the Prenuptial Agreement is not binding on third parties. Therefore, the marriage agreement is made before a notary domiciled in Indonesia so that it can be registered in Indonesia and the assets purchased become separate assets since the marriage is reported in Indonesia.